Polypharmacological Perturbation of the 14-3-3 Adaptor Protein Interactome Stimulates Neurite Outgrowth - Kaplan, Andrew; Andrei, Sebastian A; van Regteren Altena, Anna; Simas, Tristan; Banerjee, Sara L; Kato, Nobuo; Bisson, Nicolas; Higuchi, Yusuke; Ottmann, Christian; Fournier, Alyson E (Cell chemical biology, 2020)
Targeting protein-protein interactions (PPIs) is a promising approach in the development of drugs for many indications. 14-3-3 proteins are a family of phosphoprotein-binding molecules with critical functions in dozens of cell signaling networks. 14-3-3s are abundant in the central nervous system, and the small molecule fusicoccin-A (FC-A), a tool compound that can be used to manipulate 14-3-3 PPIs, enhances neurite outgrowth in cultured neurons. New semisynthetic FC-A derivatives with improved binding affinity for 14-3-3 complexes have recently been developed. Here, we use a series of screens that identify these compounds as potent inducers of neurite outgrowth through a polypharmacological mechanism. Using proteomics and X-ray crystallography, we discover that these compounds extensively regulate the 14-3-3 interactome by stabilizing specific PPIs, while disrupting others. These results provide new insights into the development of drugs to target 14-3-3 PPIs, a potential therapeutic strategy for CNS diseases.